Didanosine-loaded poly(epsilon-caprolactone) microparticles by a coaxial electrohydrodynamic atomization (CEHDA) technique. Issue 1 (4th November 2014) - Seremeta, Katia P.; Höcht, Christian; Taira, Carlos; Cortez Tornello, Pablo R.; Abraham, Gustavo A.; Sosnik, Alejandro
Abstract : EHDA technology was used to encapsulate the water-soluble antiretroviral ddI within PCL particles and stabilize it in the gastric medium where it undergoes fast degradation. Abstract : The goal of this study was to investigate the electrohydrodynamic atomization (EHDA) technology to encapsulate the water-soluble antiretroviral didanosine (ddI) within poly(epsilon-caprolactone) (PCL) particles and stabilize it in the gastric medium where it undergoes fast degradation. A preliminary study employing a one-needle setup enabled the adjustment of the critical process parameters. Then, a configuration of two concentric needles named coaxial electrohydrodynamic atomization (CEHDA) led to the formation of ddI-loaded PCL microcapsules. Scanning electron microscopy analysis showed that the microparticles were spherical and with narrow size distribution. Attenuated total reflectance/Fourier transform infrared spectroscopy confirmed that most of the drug was efficiently encapsulated within the particles, whereas differential scanning calorimetry and X-ray powder diffraction revealed that the drug was preserved mainly in crystalline form. The loading capacity was relatively high (approximately 12% w/w), and the encapsulation efficiency was approximately 100%. In vitro release assays (PBS pH = 7.4) indicated that ddI was released almost completely within 2 h. Moreover, the delayed release was expected to isolate ddI from the biological fluids during the gastric transit. Finally, pharmacokinetics studies in rats showed that ddI-loaded particles lead to a statistically significant increase of the oral bioavailability of almost 4 times and a 2-fold prolongation of the half-life with respect to a ddI aqueous solution, supporting the use of CEHDA as a promising reproducible, scalable and cost-viable technology to encapsulate water-soluble drugs within polymeric particles.